A Novel Parasitoid of Marine Dinoflagellates, Pararosarium dinoexitiosum gen. et sp. nov. (Perkinsozoa, Alveolata), Showing Characteristic Beaded Sporocytes - Jeon, Boo Seong; Park, Myung Gil (Frontiers in Microbiology, 2021)
The phylum Perkinsozoa is known as an exclusively parasitic group within alveolates and is widely distributed in various aquatic environments from marine to freshwater environments. Nonetheless, their morphology, life cycle, the identity of the host, and physiological characteristics remain still poorly understood. During intensive sampling along the west coast of Korea in October and November 2017, a new parasitoid, which shares several characteristics with the extant families Perkinsidae and Parviluciferaceae, was discovered and three strains of the new parasitoid were successfully established in cultures. Cross-infection experiments showed that among the examined planktonic groups, only dinoflagellates were susceptible to the new parasitoid, with infections observed in species belonging to eight genera. Even though the new parasitoid shared many morphological and developmental characteristics with other Perkinsozoan parasites, it differed from them by its densely packed trophocyte structure without a large vacuole or hyaline material during the growth stage. These characteristics are common among Parviluciferaceae members. Furthermore, through palintomic extracellular sporogenesis, it produced characteristic interconnected sporocytes resembling a string of beads. Phylogenetic analyses based on the small subunit and large subunit ribosomal DNA sequences revealed that the new parasitoid was distantly related to the family Parviluciferaceae and was more closely related to the families Perkinsidae and Xcellidae. Morphological, ultrastructural, and molecular data on the new parasitoid raised the need to erect a new family, i.e., Pararosariidae, within the phylum Perkinsozoa with Pararosarium dinoexitiosum gen. et sp. nov. as the type species. The isolation and establishment in culture of the new parasitoid outside the family Parviluciferaceae in the present study would contribute to the better understanding of the diversity of Perkinsozoan parasites and provide useful material for comparisons to other parasite species in the further study.